Importância do NIRS na monitorização da isquemia da medula espinal durante a reparação endovascular da aorta torácica - Moreira, Joana; Fernandes, Rita; Araújo, Ana Maria; Loureiro, Luís; NEUTEL , ELIZABETE (Journal of the Portuguese Society of Anesthesiology, 2021)
Endovascular aortic procedures are becoming increasingly common, replacing open surgical repair in the majority of patients with thoracoabominal aortic aneurysms. In these procedures, spinal cord perfusion is vulnerable. A high risk patient for spinal ischaemia was presented for a branched 22 cm long thoracic endovascular aortic repair (TEVAR) elective procedure. We used a monitoring approach with a subarachnoid catheter, according to our institutional protocol for TEVAR procedures, complemented with the use of Near-infrared spectroscopy (NIRS). Continuous non-invasive surveillance of peri-spinal oxygen supply-demand balance during the procedure (NIRS), together with mean arterial pressure and cerebrospinal fluid pressure trends, was of uttermost importance to help us distinguish the pathophysiology mechanism behind the ischemic insult and act accordingly. NIRS has the potential to satisfy all the criteria for ideal spinal cord monitoring, such as noninvasive, continuous and real-time information about spinal cord perfusion and oxygenation.